SANKSI PIDANA KEBIRI DARI PERSPEKTIF HAK ASASI MANUSIA - Sudiasa, A.A. KT. (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2017)
The results of a study of child sexual violence revealed that the scale of the number of children becoming corbantant increased. States are perceived as failures in protecting children from perpetual perpetrators of sexual violence perpetrated by irresponsible persons with children as sexual objects through trafficking, child prostitution, child pornography, and sexual harassment. Therefore, this issue needs to gain the extraordinary attention of all parties through strengthening commitments and actions at the national and local levels to keep children from the threat of deprivation of childrens rights, so that children can grow and develop optimally. In the context of human rights: repressive action with the imposition of criminal sanctions (kebiri) is very important to be done as a means of effect to the perpetrators of the perpetrators of sexual violence in children